A method for siliconizing the surface of copper alloy

Through shot peening and gas/solid co-permeable silicone process, the formation of a gradient-structured silicone layer on the surface of the copper alloy is solved, and the problems of low hardness and poor wear resistance of the copper alloy bearing are significantly improved.

CN115896684BActive Publication Date: 2025-02-14JIANGSU XINGYU NEW MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202211488637.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2025-02-14
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

During the friction and wear process, existing copper alloy bearings have problems such as low hardness, poor oxidation resistance and low wear resistance, resulting in limited service life.

Method used

By performing shot peening and gas/solid co-permeable silicone on the surface of the copper alloy, a gradient structure of silicone permeable layer is formed to improve surface hardness and bond strength.

Benefits of technology

It significantly improves the wear resistance and service life of copper alloy bearings, while enhancing its load-bearing capacity in heavy-load scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003963890980000061
    Figure BDA0003963890980000061
  • Figure BDA0003963890980000071
    Figure BDA0003963890980000071
  • Figure BDA0003963890980000081
    Figure BDA0003963890980000081
Patent Text Reader

Abstract

The present invention relates to a method for siliconizing on the surface of a copper alloy, comprising the following steps: shot peening is performed on the copper alloy to be treated; wherein the shot peening used for the shot peening is composed of a first tungsten ball with a diameter of 5mm, a second tungsten ball with a diameter of 4mm, a third tungsten ball with a diameter of 3mm, and a fourth tungsten ball with a diameter of 2mm; the time of the shot peening is 1-3h; the treated copper alloy is placed in a loading boat, and a siliconizing agent is filled in the loading boat so that the copper alloy is completely covered by the siliconizing agent; the loading boat is then placed in an atmosphere furnace, a mixed gas of silane and hydrogen is continuously passed into the atmosphere furnace, after the temperature is raised to 380-420°C, the temperature is kept for 5-8h, and the furnace is cooled and discharged. The method of the present invention can effectively improve the wear resistance of the copper alloy, improve the service life of the copper alloy, and the siliconizing process of the present invention can be carried out under low temperature conditions, without worrying about causing the copper alloy to anneal and soften while siliconizing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for siliconizing the surface of a copper alloy, belonging to the technical field of alloy material manufacturing. Background Art

[0002] Copper and its alloys are a basic nonferrous metal material widely used in the engineering field. They have high electrical and thermal conductivity, good fatigue resistance and friction and wear resistance, are easy to form and machine, and have good corrosion resistance under certain conditions. They are widely used in many departments such as electrical instrumentation, chemical industry, shipbuilding, aviation, machinery, etc.

[0003] Copper alloys are widely used as bearings. When working, they usually rub against alloy steel shafts. However, compared with alloy steel, copper alloys have shortcomings such as low strength, low hardness, poor oxidation resistance, and low wear resistance, which limit their service life. According to experience, the higher the hardness of the friction parts, the stronger the wear resistance. Therefore, improving the hardness of the working surface of copper alloys is a reliable way to improve the wear resistance and service life of copper bearings. In order to improve the above-mentioned shortcomings and defects of copper alloy bearings, scientific researchers have thought of many ways to improve them. Plating treatment methods such as electroplating, hot dip plating or chemical plating can improve their surface properties, but the effect is not ideal and there are many problems such as high energy consumption and environmental pollution. Siliconizing the surface of copper alloys is a good way to modify the surface, and there are many research results. Silicon itself is hard and is also a strengthening element of copper. Siliconizing the surface of copper alloys can achieve a gradient change from hard to harder hardness from the surface to the inner layer. This gradient structure is conducive to improving the wear resistance of the friction working surface of the copper bearing, and can also improve its bonding strength with the matrix, thereby increasing its overall life. There are many methods for siliconizing the surface of copper alloys: some use solid method for surface siliconization [1-3] , some use gas method for surface siliconization [4,5] Siliconizing copper alloys can not only improve the wear resistance of copper alloys, but also reduce the surface friction coefficient of copper alloys and increase the service life of copper alloys. It is an effective process for increasing the service life of copper bearings and has engineering promotion value. [6] .

[0004] Although the service life of copper bearings has been greatly improved after surface siliconization, the current siliconization process, whether it is a solid method or a gas method, usually has a siliconization temperature of around 750°C (temperature range is 600-900°C). When siliconizing at above 600°C, the copper alloy has generally completed complete annealing and softening, that is, the copper bearing has been completely annealed and softened. The annealing and softening of the copper substrate will reduce the load-bearing capacity of the copper bearing and is also not conducive to the service life of the copper bearing. In other words, there is still a lot of room for improvement in the current siliconization process. On the one hand, it is necessary to improve the quality of siliconization to improve wear resistance and increase the service life of copper bearings; on the other hand, it is necessary to improve the hardness and strength of the matrix to increase its service life. At the same time, it can also be used in heavy-load use scenarios to expand the application range of copper bearings.

[0005] References

[0006] 1. Li Xiaojing, Gao Yongliang, Hao Rui, et al. Study on corrosion resistance of industrial pure copper silica infiltrated layer [J]. Ordnance Material Science and Engineering, 2016, 39(1): 5-9.

[0007] 2. Ma Zhuang, An Yajun, Yang Jie, et al. Study on preparation technology and wear resistance of siliconized layer of coal gangue [J]. Nonmetallic Minerals, 2014, 37(3): 81-83.

[0008] 3. Zhao Bin, Li Xiaojing, Wu Renna, et al. Study on erosion and wear resistance of industrial pure copper silicon-infiltrated layer [J]. Heat Treatment of Metals, 2015, 40(6): 45-48.

[0009] 4. Gan Zhenghao, Mao Zhiyuan, Shen Fuchu, et al. Research on a new process of gas surface siliconization of copper [J]. Materials Science and Engineering, 1996, 14(4): 38-42.

[0010] 5. Shen Fuchu, Mao Zhiyuan, Li Jian, et al. Study on the oxidation resistance of gas siliconized coating on copper surface [J]. Corrosion Science and Protection Technology, 1997, 9(3): 205-209.

[0011] 6. Cheng Jun, Zhu Jian. Wear resistance and process control of silicon-infiltrated layer of copper alloy [J]. Journal of East China University of Science and Technology, 1998, 24(6): 710-716. Summary of the invention

[0012] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for siliconizing the surface of a copper alloy to obtain a copper alloy with excellent wear resistance and strong load-bearing capacity.

[0013] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0014] A method for siliconizing a copper alloy surface comprises the following steps:

[0015] S1. Shot peening of the copper alloy to be treated;

[0016] The shot peening treatment comprises a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm. The first tungsten ball accounts for 10-20 wt % of the shot peening treatment, the second tungsten ball accounts for 30-40 wt % of the shot peening treatment, the third tungsten ball accounts for 30-40 wt % of the shot peening treatment, and the fourth tungsten ball accounts for 10-20 wt % of the shot peening treatment. The shot peening treatment time is 1-3 h. The copper alloy to be treated contains nickel and silicon.

[0017] S2. Place the copper alloy treated by S1 in a loading boat, and fill the loading boat with siliconizing agent so that the copper alloy is completely covered by the siliconizing agent. Preferably, the thickness of the siliconizing agent above the copper alloy is 2-4 mm; then place the loading boat in an atmosphere furnace, and continuously introduce a mixed gas of silane and hydrogen into the atmosphere furnace. Preferably, maintain the pressure in the furnace at a slightly positive pressure (200-400 Pa higher than the atmospheric pressure) to ensure that fresh mixed gas continuously flows through the surface of the copper alloy and no air enters the furnace. After heating to 380-420°C, keep warm for 5-8 hours, cool and take out of the furnace.

[0018] Further, in S1, the first tungsten ball accounts for 13-17wt% in the shot peening, the second tungsten ball accounts for 33-37wt% in the shot peening, the third tungsten ball accounts for 33-37wt% in the shot peening, and the fourth tungsten ball accounts for 13-17wt% in the shot peening.

[0019] Optionally, the loading boat is a graphite boat or a corundum boat.

[0020] Further, in S2, the loading boat is placed in an atmosphere furnace, nitrogen is first charged into the atmosphere furnace to exhaust the air in the atmosphere furnace, and then a mixed gas of silane and hydrogen is introduced into the atmosphere furnace.

[0021] Furthermore, in S2, the volume ratio of silane to hydrogen in the mixed gas is 1:1-2.

[0022] Furthermore, in S2, the heating rate is 1-3°C / min.

[0023] Further, in S2, the siliconizing agent includes a silicon source, a catalyst, an anti-sintering agent and a filler. Preferably, the mass ratio of the silicon source, the catalyst, the anti-sintering agent and the filler is 65-75:3-8:5-15:10-20.

[0024] Furthermore, the silicon source is formed by mixing silicon powder and ferrosilicon powder in a mass ratio of 40-60:40-60; the infiltration catalyst is formed by mixing coal gangue powder and aluminum powder in a mass ratio of 30-40:60-70; the anti-sintering agent is formed by mixing graphite powder, lime powder and magnesia powder in a mass ratio of 30-38:30-36:30-36; the filler is formed by mixing perlite powder, quartz powder and silicon carbide powder in a mass ratio of 30-38:30-36:30-36.

[0025] Furthermore, in S2, the average particle size D50 of the siliconizing agent is 45-74 μm.

[0026] Further, in S2, the temperature is raised to 390-410°C, preferably, the temperature is raised to 395-405°C.

[0027] Optionally, the atmosphere furnace is a sealable tube furnace or box furnace.

[0028] Furthermore, in the copper alloy, the content of Ni is 5-15wt%, and further, the content of Si is 0.1-0.3wt%.

[0029] Optionally, the copper alloy is a Cu-10Ni-0.2Si alloy.

[0030] The present invention performs a gas / solid co-siliconizing process under relatively low temperature conditions, which not only maintains the substrate hardness and strength of the surface siliconized copper alloy, but also produces an aging hardness effect to significantly improve its hardness and strength. The composition and structure of the siliconized layer are more reasonable, further improving the load-bearing capacity and wear resistance of the siliconized copper alloy. It is applied to the surface treatment of related copper bearings and other workpieces, which can greatly improve the service life of copper bearings and other workpieces, and can be used in heavy-load usage scenarios.

[0031] The shot peening used in the present invention is a metal tungsten ball, and the density of tungsten is 19.35g / cm 3 , density of steel is 7.85g / cm 3The thickness of the deformation layer of the surface is much higher than that of the tungsten ball. When shot peening, the deformation layer of the surface can be much thicker, and a deformation layer of about 1 mm can be obtained. The specific tungsten ball ratio of the present invention can make the deformation layer present a gradient change very uniformly, that is, the degree of deformation becomes smaller and smaller from the surface to the inside. On the other hand, the specific tungsten ball ratio can make the deformation layer store energy more fully, and the grains are micronized or even nanometerized, which is beneficial to reduce the diffusion activation energy of silicon atoms during siliconization, and is also beneficial to the diffusion and migration of silicon atoms. The uniform gradient deformation helps to make the siliconized layer formed by subsequent siliconization present an obvious gradient change. This gradient structure can maintain a good connection between the hard and wear-resistant siliconized layer and the softer supporting center, relax or even eliminate stress. Moreover, in the copper alloy, the nickel dissolved in copper is just the aging treatment process of the copper-nickel-silicon alloy during the siliconization process. Under the joint action of the activation energy of deformation energy storage and the subgrain boundary energy, the silicon atoms and the nickel atoms can easily generate nickel-silicon intermetallic compounds. The generation mechanism of these intermetallic compound particles is different from that of the copper-nickel-silicon alloy during aging treatment. The nickel-silicon intermetallic compound particles generated during siliconization treatment are synthesized in situ when silicon atoms enter the alloy. The intermetallic compound particles generated during the aging treatment of copper-nickel-silicon alloy are generated in situ by the precipitation of supersaturated solid solution nickel and silicon atoms in the alloy during aging. Their generation paths are completely different. The nickel-silicon intermetallic compounds precipitated from the matrix are dispersed, while the nickel-silicon intermetallic compounds generated in situ in the siliconized layer are mainly located at the grain boundaries. The nickel-silicon intermetallic compounds located at the grain boundaries strongly hinder the movement of dislocations and have a significant strengthening effect on grain boundary strengthening. Better strengthening effects can be obtained than dispersed nickel-silicon intermetallic compounds, effectively improving the hardness of the siliconized layer. The process of generating these intermetallic compound hard particle phases, namely the siliconization process, will also produce an aging hardening strengthening effect. Its strengthening and hardening mechanisms are different at different locations. In the siliconized layer on the surface, the deformation and grain refinement of the siliconized composite mixed tungsten ball shot peening, and the aging of the base copper alloy will produce three strengthening mechanisms: 1) the precipitation strengthening of the nickel-silicon intermetallic compound generated during the aging of the base copper alloy, 2) the grain boundary strengthening of the nickel-silicon intermetallic compound generated in situ in the siliconized layer, and 3) the deformation strengthening of the siliconized layer before siliconization, which makes the hardness of the siliconized layer more obvious; through the mixed tungsten ball shot peening treatment, the surface of the copper alloy has produced strong deformation and grain refinement, which provides sufficient activation energy for the siliconization process, helps to greatly reduce the siliconization temperature and achieve good results. The base copper-nickel-silicon alloy will produce an aging hardening effect during the siliconization process, which is an effect that other copper alloys such as H60 brass or white copper cannot achieve.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The method of the present invention can effectively improve the wear resistance of the working surface of the copper bearing and increase the service life of the copper alloy.

[0034] (2) The method of the present invention can effectively improve the strength of the copper bearing matrix, increase its service life, and at the same time improve its load-bearing capacity, and can be applied to heavy-load scenarios to expand its scope of use.

[0035] (3) The siliconizing process of the present invention can be carried out under low temperature conditions. Siliconizing will not cause annealing and softening of the base copper alloy, but will produce a hardening effect, so that the copper alloy base itself is hardened.

[0036] (4) The process of the present invention is simple and efficient, and can be completed using existing equipment and siliconizing technology. The cost is low, so it is easy to implement and can be promoted and applied on an industrial scale. DETAILED DESCRIPTION

[0037] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0038] Example 1

[0039] In this embodiment, the method of siliconizing the copper alloy surface is as follows:

[0040] (1) The surface of the copper alloy ring made of Cu-10Ni-0.2Si and the copper plate made of Cu-10Ni-0.2Si were shot peened for 2 h respectively;

[0041] The shot peening used for the shot peening treatment consists of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm. The first tungsten ball accounts for 15wt% of the shot peening, the second tungsten ball accounts for 35wt% of the shot peening, the third tungsten ball accounts for 35wt% of the shot peening, and the fourth tungsten ball accounts for 15wt% of the shot peening;

[0042] (2) Place the workpiece processed in step 1 (i.e., the copper alloy ring and copper plate) into a corundum boat, and fill the loading boat with siliconizing agent so that the copper alloy is completely covered with the siliconizing agent with a thickness of 3 mm; then place the loading boat into a sealable box furnace, fill the furnace chamber of the sealed box furnace with nitrogen, and after the air is expelled by the nitrogen, continuously introduce a mixed gas of silane and hydrogen into the box furnace, and maintain the pressure in the furnace at a slightly positive pressure (300Pa higher than the atmospheric pressure) to ensure that fresh mixed gas continuously flows through the surface of the copper alloy and no air enters the furnace, and ignite at the outlet. Turn on the power to increase the temperature, and after heating to 380°C at a rate of 1.5°C / min, keep warm for 5 hours, cool to room temperature with the furnace, and then take out of the furnace;

[0043] Wherein, in the mixed gas, the volume ratio of silane to hydrogen is 1:1.5;

[0044] The siliconizing agent is composed of a silicon source, a catalyst, an anti-sintering agent and a filler in a mass ratio of 75:10:15. The silicon source is a mixture of 40wt% silicon powder and 60wt% ferrosilicon powder; the catalyst is a mixture of gangue powder and aluminum powder in a mass ratio of 35:65; the anti-sintering agent is a mixture of graphite powder, lime powder and magnesia powder in a mass ratio of 34:33:33; the filler is a mixture of pearlite powder, quartz powder and silicon carbide powder in a mass ratio of 34:33:33. The average particle size D50 of the siliconizing agent is 50μm.

[0045] The friction and wear test was carried out on the copper alloy ring, and the ring-shaped dual friction and wear test was completed on the MMW-1A testing machine under dry friction conditions. The inner diameter of the copper alloy ring was 25±0.02mm, the outer diameter was 28±0.02mm, and the height was 5±0.02mm.

[0046] Samples were taken from the copper plate and hardness tested using an American Wilson RB2000 fully automatic Rockwell hardness tester. Microhardness was measured at different positions from the upper surface to the center of the cross section perpendicular to the copper plate surface.

[0047] Embodiment 2-9

[0048] Example 1 was repeated, except that the contents shown in Table 1 and Table 2 were different.

[0049] Comparative Examples 1-15

[0050] Example 1 was repeated, except that the contents shown in Table 1 and Table 2 were different.

[0051] The hardness test results of each embodiment and comparative example are shown in Table 1, and the dry friction and wear test results are shown in Table 2, wherein the experimental data in each table are the average values ​​of the relevant experimental data of 20 samples.

[0052] Table 1 Hardness of different positions of the cross section of Cu-10Ni-0.2Si copper plate after siliconization treatment

[0053]

[0054]

[0055]

[0056]

[0057]

[0058]

[0059]

[0060] In Table 1: - indicates no operation

[0061] (1) indicates that the shot used for shot peening is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm, the first tungsten ball accounts for 15wt% of the shot, the second tungsten ball accounts for 35wt% of the shot, the third tungsten ball accounts for 35wt% of the shot, and the fourth tungsten ball accounts for 15wt% of the shot;

[0062] (2) indicates that the shot used for shot peening is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm, the first tungsten ball accounts for 20 wt% of the shot, the second tungsten ball accounts for 35 wt% of the shot, the third tungsten ball accounts for 30 wt% of the shot, and the fourth tungsten ball accounts for 15 wt% of the shot;

[0063] (3) indicates that the shot used for shot peening is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm, the first tungsten ball accounts for 15wt% of the shot, the second tungsten ball accounts for 30wt% of the shot, the third tungsten ball accounts for 35wt% of the shot, and the fourth tungsten ball accounts for 20wt% of the shot;

[0064] (4) means that the tungsten ball is replaced by a steel ball (a steel ball made of stainless steel), and other conditions remain unchanged.

[0065] (5) indicates that the shot used in the shot peening process consists of a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm, and the mass ratio of the second tungsten ball, the third tungsten ball, and the fourth tungsten ball is 35:35:15;

[0066] (6) indicates that the shot used for the shot peening treatment consists of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, and a third tungsten ball with a diameter of 3 mm, and the mass ratio of the first tungsten ball, the second tungsten ball, and the third tungsten ball is 15:35:35.

[0067] (7) indicates that the materials of the copper alloy ring and the copper plate are both H60 brass.

[0068] (8) indicates that the shot peening treatment is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm. The first tungsten ball accounts for 8wt% of the shot peening, the second tungsten ball accounts for 42wt% of the shot peening, the third tungsten ball accounts for 42wt% of the shot peening, and the fourth tungsten ball accounts for 8wt% of the shot peening.

[0069] (9) indicates that the shot peening used is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm. The first tungsten ball accounts for 22wt% of the shot peening, the second tungsten ball accounts for 28wt% of the shot peening, the third tungsten ball accounts for 28wt% of the shot peening, and the fourth tungsten ball accounts for 22wt% of the shot peening.

[0070] Table 2 Dry friction and wear test results of Cu-10Ni-0.2Si copper alloy ring before and after siliconization treatment

[0071]

[0072]

[0073] In Table 2: - indicates no operation

[0074] (1) indicates that the shot used for shot peening is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm, the first tungsten ball accounts for 15wt% of the shot, the second tungsten ball accounts for 35wt% of the shot, the third tungsten ball accounts for 35wt% of the shot, and the fourth tungsten ball accounts for 15wt% of the shot;

[0075] (2) indicates that the shot used for shot peening is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm, the first tungsten ball accounts for 20 wt% of the shot, the second tungsten ball accounts for 35 wt% of the shot, the third tungsten ball accounts for 30 wt% of the shot, and the fourth tungsten ball accounts for 15 wt% of the shot;

[0076] (3) indicates that the shot used for shot peening is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm, the first tungsten ball accounts for 15wt% of the shot, the second tungsten ball accounts for 30wt% of the shot, the third tungsten ball accounts for 35wt% of the shot, and the fourth tungsten ball accounts for 20wt% of the shot;

[0077] (4) means that the tungsten ball is replaced by a steel ball (a steel ball made of stainless steel), and other conditions remain unchanged.

[0078] (5) indicates that the shot used in the shot peening process consists of a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm, and the mass ratio of the second tungsten ball, the third tungsten ball, and the fourth tungsten ball is 35:35:15;

[0079] (6) indicates that the shot used for the shot peening treatment consists of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, and a third tungsten ball with a diameter of 3 mm, and the mass ratio of the first tungsten ball, the second tungsten ball, and the third tungsten ball is 15:35:35.

[0080] (7) indicates that the copper bearing and copper plate are made of H60 brass.

[0081] (8) indicates that the shot peening treatment is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm. The first tungsten ball accounts for 8wt% of the shot peening, the second tungsten ball accounts for 42wt% of the shot peening, the third tungsten ball accounts for 42wt% of the shot peening, and the fourth tungsten ball accounts for 8wt% of the shot peening.

[0082] (9) indicates that the shot peening used is composed of a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm. The first tungsten ball accounts for 22wt% of the shot peening, the second tungsten ball accounts for 28wt% of the shot peening, the third tungsten ball accounts for 28wt% of the shot peening, and the fourth tungsten ball accounts for 22wt% of the shot peening.

[0083] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A method for siliconizing a copper alloy surface, characterized in that: The steps include: S1. Shot peening of the copper alloy to be treated; The shot peening treatment comprises a first tungsten ball with a diameter of 5 mm, a second tungsten ball with a diameter of 4 mm, a third tungsten ball with a diameter of 3 mm, and a fourth tungsten ball with a diameter of 2 mm. The first tungsten ball accounts for 10-20wt% of the shot peening treatment, the second tungsten ball accounts for 30-40wt% of the shot peening treatment, the third tungsten ball accounts for 30-40wt% of the shot peening treatment, and the fourth tungsten ball accounts for 10-20wt% of the shot peening treatment. The shot peening treatment time is 1-3h. The copper alloy to be treated contains nickel and silicon. S2. Place the copper alloy treated by S1 in a loading boat, and fill the loading boat with siliconizing agent so that the copper alloy is completely covered by the siliconizing agent; then place the loading boat in an atmosphere furnace, continuously introduce a mixed gas of silane and hydrogen into the atmosphere furnace, heat it to 380-420°C, keep it warm for 5-8h, cool it down and take it out of the furnace.

2. The method according to claim 1, characterized in that In S1, the first tungsten ball accounts for 13-17wt% of the shot peening, the second tungsten ball accounts for 33-37wt% of the shot peening, the third tungsten ball accounts for 33-37wt% of the shot peening, and the fourth tungsten ball accounts for 13-17wt% of the shot peening.

3. The method according to claim 1, characterized in that In S2, the volume ratio of silane to hydrogen in the mixed gas is 1:1-2.

4. The method according to claim 1, characterized in that In S2, the heating rate is 1-3°C / min.

5. The method according to claim 1, characterized in that In S2, the siliconizing agent includes a silicon source, a catalyst, an anti-sintering agent and a filler.

6. The method according to claim 5, characterized in that The mass ratio of the silicon source, the infiltration catalyst, the anti-sintering agent and the filler is 65-75:3-8:5-15:10-20.

7. The method according to claim 5, characterized in that The silicon source is formed by mixing silicon powder and ferrosilicon powder in a mass ratio of 40-60:40-60; the infiltration catalyst is formed by mixing coal gangue powder and aluminum powder in a mass ratio of 30-40:60-70; the anti-sintering agent is formed by mixing graphite powder, lime powder and magnesia powder in a mass ratio of 30-38:30-36:30-36; the filler is formed by mixing perlite powder, quartz powder and silicon carbide powder in a mass ratio of 30-38:30-36:30-36.

8. The method according to claim 1, characterized in that In S2, the average particle size D50 of the siliconizing agent is 45-74 μm.

9. The method according to any one of claims 1 to 8, characterized in that: In the copper alloy, the content of Ni is 5-15wt%.

10. The method according to any one of claims 1 to 8, characterized in that: In the copper alloy, the content of Si is 0.1-0.3wt%.

Citation Information

Patent Citations

  • Method for coating or metallization on copper matrix

    CN1050571A

  • Preparation method of carbon ceramic automobile brake disc

    CN110372389A

Cited By

  • A method of manufacturing a copper alloy member

    CN122895443A